Consensus guidelines for the diagnosis and management of invasive aspergillosis, 2021. (22nd December 2021) - Douglas, Abby P.; Smibert, Olivia. C.; Bajel, Ashish; Halliday, Catriona L.; Lavee, Orly; McMullan, Brendan; Yong, Michelle K.; van Hal, Sebastiaan J.; Chen, Sharon C.‐A.
Abstract: Invasive aspergillosis (IA) in haematology/oncology patients presents as primary infection or breakthrough infection, which can become refractory to antifungal treatment and has a high associated mortality. Other emerging patient risk groups include patients in the intensive care setting with severe respiratory viral infections, including COVID‐19. These guidelines present key diagnostic and treatment recommendations in light of advances in knowledge since the previous guidelines in 2014. Culture and histological‐based methods remain central to the diagnosis of IA. There is increasing evidence for the utility of non‐culture methods employing fungal biomarkers in pre‐emptive screening for infection, as well as for IA diagnosis when used in combination. Although azole resistance appears to be uncommon in Australia, susceptibility testing of clinical Aspergillus fumigatus complex isolates is recommended. Voriconazole remains the preferred first‐line antifungal agent for treating primary IA, including for extrapulmonary disease. Recommendations for paediatric treatment broadly follow those for adults. For breakthrough and refractory IA, a change in class of antifungal agent is strongly recommended, and agents under clinical trial may need to be considered. Newer immunological‐based imaging modalities warrant further study, while surveillance for IA and antifungal resistance remain essential to informing the relevance of current treatment recommendations.